Problemas de comportamento de filhos na opinião de mães e pais definições, características e causas - Aline Maira Silva; Fabiana Cia (Universidade Estadual Paulista Júlio de Mesquita Filho, 2012)
The causes and characteristics of the behavior problems are diverse and describe this phenomenon is important in order to promote educational interventions. This study aimed to examining parental knowledge about behavioral problems. The participants were 79 parents of preschool children and schoolchildren who completed a questionnaire composed of five questions. With respect to their knowledge about child behavioral problems, parents described their perceptions such as: misbehavior, inappropriate attitudes and habits; behavior deviations; divergent patterns of behavior; disruptive behavior; and difficulty in knowing how to behave. Regarding the characteristics of externalizing behavior problems, according to parents their children behave aggressively and have temper tantrums, and with respect to internalizing behavior problems parents highlighted isolation and low self-esteem. Concerning the causes of behavior problems, they emphasized family factors as determinants of child outcome. The data provide information on the issue of behavior problems is understood by parents, helping to support interventions with a focus to guide families on the prevention of behavioral problems.